TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI SEBELUM DAN SESUDAH MELAKUKAN TERAPI RELAKSASI BENSON DI GRIYA KASIH SILOAM HOSPITAL MALANG - zainol rachman; Sofi Prima Wahyu Sejati; Edy Suyanto; Ekowati Retnaningtyas (Jurnal Informasi Kesehatan Indonesia (JIKI), 2021)
Benson relaxation combines relaxation response techniques and individual faith systems (focused on certain expressions of God's names, or words that have a calming meaning to the patient itself) that is repeated over and over with regular rhythms accompanied by resignation. Relaxation Benson is useful to overcome high blood pressure and heart irregularity if done with good technique and correct with the frequency of exercise with 10-15 minutes each time the exercise. This case study aims to identify blood pressure picture in elderly who have hypertension before and after doing benson relaxation therapy. This research method is Descriptive Case Study with subject subject as much as 2 subjects conducted on January 14 to January 27, 2018 with systole blood pressure> 140 mmHg and diastole <90 or> 90 mmHg. In subject I from the observation of the mean initial blood pressure 142/90 mmHg and the mean final blood pressure after ergonomic gym exercises 130/80 mmHg. While on the subject II average initial blood pressure before benson relaxation 146/90 mmHg and after the relaxation of the average benson 133/83 mmHg. The results of the case study found that after benson relaxation both subjects experienced a decrease in blood pressure. The recommendations of the study are regular benson relaxation exercises with good and correct technique capable of lowering blood pressure in the elderly with hypertension and suppressing the incidence of hypertension in the elderly.